1995
DOI: 10.2187/bss.9.327
|View full text |Cite
|
Sign up to set email alerts
|

Several aspects on the plant growth and development in space environment. The senescence of oat leaf segments is promoted under simulated microgravity condition on a three-dimensional clinostat.

Abstract: Miyamoto, K. et al. condition on promoting the senescence is also discussed. Materials and methodsThe senescence of oat leaf segments under simulated microgravity on a 3-D clinostat was studied according to the methods previously reported with modifications (Ueda and Kato 1980, Hoson et al. 1992.Oat (Avena sativa L. cv Victory) seeds were germinated in vermiculite under continuous white fluorescent light of 5 W/m 2 at 25 ˚C for 9 days on 1 xg condition. The first leaves were harvested and 3-cm segments of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…This evidence suggests that the photosynthetic inhibition is caused by destruction of the photosynthetic system. The results recorded in our experiment are in agreement with those reported by Miyamoto et al (1995Miyamoto et al ( , 2001 who observed that simulated microgravity conditions enhanced the loss of chlorophyll in oat leaf segments due to alterations of the physiological process of leaf senescence (e.g. protease activity) and the dynamics of endogenous plant hormone levels (e.g.…”
Section: Resultssupporting
confidence: 93%
“…This evidence suggests that the photosynthetic inhibition is caused by destruction of the photosynthetic system. The results recorded in our experiment are in agreement with those reported by Miyamoto et al (1995Miyamoto et al ( , 2001 who observed that simulated microgravity conditions enhanced the loss of chlorophyll in oat leaf segments due to alterations of the physiological process of leaf senescence (e.g. protease activity) and the dynamics of endogenous plant hormone levels (e.g.…”
Section: Resultssupporting
confidence: 93%